PENGARUH LATIHAN PLYOMETRIC TERHADAP KECEPATAN TENDANGAN MAWASHI GERI - Kadir, Suprianto; Duhe, Edy Dharma Putra; Irawan, Safri; Haryani, Meri; Suardika, I Kadek; Aalang, Christin Gloria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of resistance band training on the speed of the *gyaku tsuki* punch among students of the Sports Coaching Education Study Program at Gorontalo State University (UNG). The study employed a quantitative approach using an experimental method and a one-group pretest-posttest design. The sample consisted of 30 students (19 male and 11 female), selected using a total sampling technique. Data collection involved a 30-second *gyaku tsuki* punch speed test. The intervention consisted of resistance band training administered over four weeks with a frequency of three sessions per week. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and a paired-sample t-test at a significance level of 0.05. The results showed a mean pretest score of 57.07 punches/30 seconds and a mean posttest score of 65.80 punches/30 seconds, representing an increase of 8.73 punches or 15.30%. The paired-sample t-test yielded a significance value of 0.000 (p < 0.05). Thus, resistance band training had a significant effect on improving *gyaku tsuki* punch speed among UNG Sports Coaching Education students. These findings indicate that resistance bands offer a practical, economical, and relevant training alternative for karate instruction in a university setting, allowing for systematic and measurable progress.